2023
DOI: 10.3390/insects14060541
|View full text |Cite
|
Sign up to set email alerts
|

Are Appearances Deceiving? Morpho-Genetic Complexity of the Eumerus tricolor Group (Diptera: Syrphidae) in Europe, with a Focus on the Iberian Peninsula

Abstract: Eumerus Meigen, 1822 is one of the largest Syrphidae genera in the Palaearctic Region, with the highest levels of taxonomic diversity found in the Eumerus tricolor species group. Despite its high diversity, the interspecific levels of morphological variability can be low. Additionally, some species may show certain levels of intraspecific variability. Hence, species delimitation may become challenging. In this work, we assessed the diversity of the E. tricolor group in the Iberian Peninsula through an integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Despite its utility, however, DNA barcoding is not a panacea for the study of biodiversity. An integrative taxonomical approach including physiological and ecological features must be prioritised (e.g., Aguado-Aranda et al [ 13 ]; Porco et al [ 47 ]) since it provides additional data useful for separating cryptic diversity even in common species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its utility, however, DNA barcoding is not a panacea for the study of biodiversity. An integrative taxonomical approach including physiological and ecological features must be prioritised (e.g., Aguado-Aranda et al [ 13 ]; Porco et al [ 47 ]) since it provides additional data useful for separating cryptic diversity even in common species.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these Afrotropical species were described centuries ago, and their morphological diagnoses have been used in various studies without thorough revisions to encompass as much species diversity as found within the region [ 11 , 12 ]. Although morphological diagnoses have their limitations, the method is very useful when used with molecular techniques [ 13 ]. This indicates the need to use an informative and effective molecular technique to assist in morphological identification as a prerequisite for efficient conservation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this type of analysis, an approach combining different sources of data (morphological, genomic, and morphometrics) provides evolutionary clarification (e.g., [14,15]). However, as for phenotypic features, molecular features can also be variable; for example, while low interspecific variation in COI was revealed for certain species of the Eumerus tricolor (Fabricius, 1798) group [16], high levels of intraspecific variability (same molecular marker) have been found in another six Eumerus species from the Mediterranean basin [17].…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary examination of material of the E. barbarus group from the islands and mainland from the western Mediterranean basin revealed a high morphological variability, mainly in E. barbarus and E. sulcitibius. Although previous studies have assessed variability using molecular markers for other Merodontini (e.g., [22]), few studies have assessed it in Eumerus (e.g., [16]). Therefore, the main aim of this work is to explore the phenotypic variability of the species of the E. barbarus group from the western Mediterranean basin in correlation with genetic data.…”
Section: Introductionmentioning
confidence: 99%